Charles Darwin and The origin of species - Karp, Walter (London : Cassell, 1969)
A biography of the naturalist who presented the world with the theory of evolution by natural selection. Examines Darwin's voyage on the Beagle, the long years of work and illness, the principles of his theory, and their reception by the scientists and populace of nineteenth century England. Paintings, drawings, and photographs illustrate Darwin's personal life and professional studies.
Bibliography : p. 150.
Keywords: Darwin, Charles, -- 1809 - 1882